The taxonomy of the cricket subfamily Phaloriinae (Orthoptera: Grylloidea) in the Philippines - Gorochov, Andrei V.; Daguplo, Jiandy; Tan, Ming Kai (Zootaxa, 2026)
Presently, the Philippines has 17 species of crickets from the subfamily Phaloriinae. Based on new material collected recently, five species are found to be new and are described here: Phaloria (Phaloria) mindanao sp. nov., Ph. (Ph.) hamata sp. nov., Ph. (Ph.) luzoni sp. nov., Ph. (Ph.) propinqua sp. nov., and Pseudotrellius paraiso gen. et sp. nov. New data on distribution of Ph. (Ph.) amplipennis Stål, 1877, Tremellia fratercula (Chopard, 1937), Trellius (Protrellius) dulcis Gorochov, 1996, and Vescelia variegata (Chopard, 1937) in the Philippines are also given.